Label-free sorting of soft microparticles using a bioinspired synthetic cilia array - Sohrabi, Salman; Tan, Jifu; Yunus, Doruk Erdem; He, Ran; Liu, Yaling (Amer Inst Physics, 2018)
Isolating cells of interest from a heterogeneous population has been of critical importance in biological studies and clinical applications. In this study, a novel approach is proposed for utilizing an active ciliary system in microfluidic devices to separate particles based on their physical properties. In this approach, the bottom of the microchannel is covered with an equally spaced cilia array of various patterns which is actuated by an external stimuli. 3D simulations are carried out to study cilia-particle interaction and isolation dynamic in a microfluidic channel. It is observed that these elastic hair-like filaments can influence particle's trajectories differently depending on their biophysical properties. This modeling study utilizes immersed boundary method coupled with the lattice Boltzmann method. Soft particles and cilia are implemented through the spring connected network model and point-particle scheme, respectively. It is shown that cilia array with proper stimulation is able to continuously and non-destructively separate cells into subpopulations based on their size, shape, and stiffness. At the end, a design map for fabrication of a programmable microfluidic device capable of isolating various subpopulations of cells is developed. This biocompatible, label-free design can separate cells/soft microparticles with high throughput which can greatly complement existing separation technologies. Published by AIP Publishing.
2nd International Conference on Nanotechnology in Medicine -- JUN, 2018 -- Albufeira, PORTUGAL
Keywords: [No Keywords]